Exploring the locus of envelopes: an initial approach with GeoGebra - Ana Paiva; Franscisco Alves; Helena Campos (Millenium)
Introduction: The teaching of Ordinary Differential Equations (ODEs) presents significant challenges, particularly due to the predominance of algebraic methods that often limit the exploration of qualitative behaviors. The mathematical concept of an envelope, understood as the geometric locus formed by a family of curves, offers a visual and structural approach that may enrich the teaching of ODEs in a more intuitive and exploratory way.